Comparison of alternative methods for methyl acetate + methanol + acetic acid + acetic anhydride mixture separation - A. V. Frolkova; Yu. I. Shashkova; А. К. Frolkova; М. A. Mayevskiy (Тонкие химические технологии, 2019)
Objectives. The paper is a comparative analysis of methyl acetate + methanol + acetic acid + acetic anhydride industrial mixture separation flowsheets based on the use of special distillation methods (extractive distillation and pressure-swing distillation). The results obtained illustrate the variability of the structure of the technological separation flowsheet.Methods. Mathematical modeling using the software package Aspen Plus V. 10.0 was chosen as the research method. The simulation was based on the local composition equation NRTL and the Hayden–O’Connell equation of state. The relative uncertainties of phase equilibrium description do not exceed 3%.Results. The vapor–liquid diagram of the quaternary mixture of methyl acetate + methanol + acetic acid + acetic anhydride was studied using thermodynamic topological analysis. It was shown that the system contains one binary azeotrope and is characterized by one distillation region. Although the structure is not complex, there is a possibility of using several methods for mixture separation: pressure-swing distillation, and extractive distillation with different entrainers. Twelve flowsheets with different structure were proposed, and 29 variants of separation were compared.Conclusions. It was shown that the most perspective structure for the separation of a methyl acetate + methanol + acetic acid + acetic anhydride mixture is a combination of distributed sequence separation and extractive distillation.